Analisis Kritis Peran Pendidikan Kewarganegaraan dalam Mencegah Cyber Radicalism di Kalangan Gen Z: Critical Analysis of the Role of Citizenship Education in Preventing Cyber Radicalism Among Gen Z - Ahmad Muhamad Mustain Nasoha; Nazila Riskiya Putri; Yesha Renata Andyne R; Rahmania Nur Aslami; Awalia Rindu Az Zahra (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Civic education (PKn) plays a strategic role in shaping civil awareness and democratic values among the younger generation, particularly Generation Z, who were born in the digital era. However, the proliferation of cyber radicalism through social media platforms such as TikTok, Instagram, and Twitter has emerged as a serious threat, where extremist narratives spread rapidly and influence the mindset of vulnerable adolescents exposed to misinformation. This study conducts a critical analysis of the role of civic education in preventing cyber radicalism among Gen Z, focusing on curriculum, teaching methods, and the integration of digital literacy. Employing a qualitative approach based on Jürgen Habermas's critical theory of communication and the digital public sphere, this study critiques the weaknesses of the current education system, which remains insufficiently adaptive to cyber dynamics, such as the lack of empirically based anti-radicalism modules. Key findings indicate that innovative civic education, including project-based approaches and collaborations with digital platforms, can enhance the ideological resilience of Gen Z against radical propaganda, with an effectiveness rate of up to 70% based on case studies in Indonesian schools. However, challenges such as uneven internet access and cultural resistance must be addressed through national policies. This research recommends curriculum reforms in civic education to integrate cyber anti-radicalism education as an integral part of fostering critical and inclusive citizens.